Cultivation Of Religious Tolerance Values In Multicultural Al-Islam And Kemuhammadiyahan Education At Maumere Muhammadiyah University - Siti Farida; Tobroni; Nurul Humaidi (South Sulawesi Education Development (SSED), 2024)
This research focuses on the cultivation of religious tolerance values in learning Al-Islam and Kemuhammadiyahan (AIK) at Muhammadiyah Maumere University. With the background of the majority of non-Muslim students, this study aims to describe the concept of religious tolerance, the strategy of instilling values, and the results of implementation in multicultural AIK learning. The research used a descriptive qualitative approach with data collection techniques in the form of interviews, observations, and documentation. The results showed that the concept of religious tolerance is implemented through a multicultural AIK curriculum that includes an introduction to world religions, Islamic ethics, and Kemuhammadiyahan studies. The strategies used involve discussion methods, problem-based learning, contextual learning, and active and cooperative approaches. The material presented is designed to encourage understanding across religions and cultures. The cultivation of tolerance values is also carried out through extracurricular activities, such as joint studies of Muslim and non-Muslim students. The implementation results show an increase in students' understanding of diversity, the creation of a harmonious atmosphere on campus, and the strengthening of tolerance values in everyday life. Students respect and support each other's religious freedom, which leads to the formation of inclusive and responsible characters. The findings confirm the importance of multicultural-based education in building harmony and preventing interfaith conflict.